Immunohistochemical Characterization of PepT1 and Ghrelin in Gastrointestinal Tract of Zebrafish: Effects of Spirulina Vegetarian Diet on the Neuroendocrine System Cells After Alimentary Stress - Lo Cascio, Patrizia; Calabrò, Concetta; Bertuccio, Clara; Iaria, Carmelo; Marino, Fabio; Denaro, Maria G. (Frontiers in Physiology, 2018)
Gastrointestinal function in vertebrates is influenced by stressors, such as fasting and refeeding, different types of diet and hormonal factors. The aim of this paper was to analyse the effect of a Spirulina (Arthrospira platensis) diet, a microalga known for its nutraceutical properties, on the gastrointestinal tract of zebrafish (Danio rerio) regarding expression of oligopeptide transporter 1 (PepT1) and ghrelin (GHR). Food deprivation and refeeding was investigated to elucidate expression of PepT1 and GHR at a gastrointestinal level and the zebrafish compensatory mechanism. PepT1 is responsible for absorbing di- and tripeptides through a brush border membrane of intestinal mucosa. GHR is a brain-gut peptide in fish and mammals, stimulating growth hormone secretion and regulating appetite. Samples were taken after 2 and 5 days of specimen fasting, and 2 and 5 days of refeeding with Sera Spirulina tabs, in which the major constituent is Spirulina sp. (50.2% protein). Morphological and immunohistochemical analysis of PepT1 and GHR were carried out. Control specimen intestinal tract showed normal morphology of the digestive tract. Fasting caused fold structural changes and intestinal lumen constriction. Immunohistochemical analysis showed a PepT1 level reduction after fasting and an increase after refeeding, reaching very high levels after 5 days, compared to controls. GHR levels increased after food deprivation and gradually decreased after refeeding. Increased expression of PepT1 in refeeding fish suggests a compensatory physiological mechanism, as does the increase in GHR levels in fasting fish followed by a reduction after refeeding. A compensatory mechanism may be induced by fasting and refeeding and by a higher protein Spirulina diet. The microalga, for its nutraceutical properties, is an excellent candidate for animal breeding and human diet.